Strengthening Shadow Teacher Competence in Recognizing, Understanding and Supporting Children with Special Needs: Penguatan Kompetensi Shadow Teacher dalam Mengenali, Memahami, dan Mendampingi Anak Berkebutuhan Khusus - Saadah, Miftahul Aula; Mulyanti, Mulyani; Hairina, Yulia (CONSEN: Indonesian Journal of Community Services and Engagement, 2026)
Shadow teachers play an important role in assisting children with special needs. However, many shadow teachers still need to improve their understanding and skills to effectively support children with disabilities in the learning process. This workshop aims to provide knowledge and practical skills relevant  to the role of shadow teachers. Community service activities are carried out using the Service Learning (SL) method in several inclusive schools in Banjarmasin. The workshop activities were held offline well and smoothly on Saturday, August 24, 2024. This activity was designed in the form of a workshop using interactive lecture, discussion, and case study methods to enrich the participants' insights. The materials presented included an understanding of the roles and responsibilities of shadow teachers, techniques for recognizing and understanding the needs of children with disabilities, and the preparation of Individualized Education Programs (IEPs). The workshop succeeded in strengthening shadow teachers' competencies in assisting children with disabilities, with evaluation results showing that 92.3% of participants experienced a positive shift in perception of their roles, 69.2% rated the materials as highly relevant (score 5), and 65.4% rated the facilitators’ delivery as very clear (score 5), increasing their understanding of their important role in inclusive education and preparing them to face challenges in the field. Recommendations for future similar activities include increasing the duration of discussion and practice sessions and using more real-life case examples to deepen participants' understanding